The United Nations World Summit - what's at stake? - Klotzle, Kurt (2005)
Abstract: "Conspicuous foreign policy failures in Rwanda and Sudan, acrimonious disunity over Iraq, and highly publicized internal scandals have made clearer than ever before: the United Nations is in dire need of reform. Yet an ambitious reform agenda to be addressed by world leaders at the UN World Summit on 14-16 September appears in danger of failure. What are the major issues that will be on the negotiating table, and what obstacles are standing in the way of a successful outcome? This report has been produced within the framework of 'Europe's Global Responsibility,' a project implemented jointly by the Bertelsmann Stiftung and the Center for Applied Policy Research." (author's abstract)